Privacy–preserving ID–based key agreement protocols for cluster–based MANETs. (18th September 2013) - Park, YoHan; Park, YoungHo; Moon, SangJae
Security support is a significant factor in ad hoc networks. Especially in dynamic topologies, considering clusters, key distribution, key agreement and key management are essential for providing a secure system. It is also necessary to protect the identities of individual nodes in wireless environments to avoid personal privacy concerns. However, many of the existing key agreement schemes for Mobile Ad Hoc Networks (MANETs) do not consider these security issues concurrently. This paper proposes privacy–preserving ID–based cluster key distribution and key agreement schemes for cluster–based MANETs and proves them in ID–mBJM model. To the best of our knowledge, our proposal is the first in which the anonymity property is combined with cluster–based MANETs. These schemes are secure against a wide variety of attacks and are suitable for privacy–preserving MANETs. Therefore, these schemes can be applied in many different kinds of cluster–based MANETs to protect user's privacy.